Assessment and selection of M3 generation of wheat mutants adaptive in lowland. (May 2018) - Nasaruddin,; Farid, M; Musa, Y; Iswoyo, H
Abstract: Wheat is a sub-tropical plant which adaptability in the tropics in areas with altitudes over 1000 m above sea level (asl). Cultivation on the highlands is in competition with vegetables and fruits in terms of land use, therefore, it is essential to have wheat genotypes adaptive to the lowlands. This study aimed to test and select offspring of three adaptive mutant on lowland with high temperature ranged from 28 to 33°C. The benefit of the research is to obtain a potential strain of adaptive wheat mutants in the lowlands. The experiment was conducted at Experimental farm of Agriculture Faculty, Hasanuddin University Makassar at an altitude below 50 m from sea level. The study was conducted from March to June 2017. The experimental study applied a randomized block design with three replications. The treatments consisted of 20 mutants of wheat with 4 varieties used for comparison. They were Nias, Selayar, Dewata, and Munal. Results showed that the wheat mutant N.300 4.3.6 (1.92 t per hectare) gave highest growth and production and was significantly different from all other mutants and comparing varieties. The mutant genotypes that gave higher growth and production than all comparing varieties were N.350 3.1.4 (1.86 t per hectare), N.200 2.3.3 (1.67 t per hectare), N. 250 4.2.1 (1.48 t per hectare), N.200 2.4.B.6 (1.36 t per hectare), N.250 4.5.2 (1.26 t per hectare), N.350 3.2.2 (1.26 t per hectare), and N.350 3.1.3 (1.22 t per hectare). Mutants that produce higher yields than the three comparing varieties (Dewata, Selayar and Munal) with yields > 1 t per hectare, yet lower than Nias varieties (1.15 t per hectare) are N.200 2.5.2 (1.11 t per hectare), N.250 4.6.2 (1.14 t per hectare), and N.350 3.6.2 (1.07 t per hectare. In conclusion, there are 11 potential mutant genotypes for further experiment in order to develop adaptive wheat to lowlands.